2020
DOI: 10.1017/s193029750000694x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing a domain-specific risk-taking construct: A meta-analysis of reliability of the DOSPERT scale

Abstract: The DOSPERT scale has been used extensively to understand individual differences in risk attitudes across varying decision domains since 2002. The present study reports a reliability generalization meta-analysis to summarize the internal consistency of both the initial and the revised versions of DOSPERT. It also examined factors that can influence the reliability of the DOSPERT and its subscales. A total of 104 samples (N = 30,109) that reported 465 coefficient alphas were analyzed. Results of meta-regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 118 publications
(71 reference statements)
0
15
0
Order By: Relevance
“…Despite its popularity, several measurement issues regarding the internal structural validity of the DOSPERT have been found. The meta-analysis by Shou and Olney (2020a) found that the reliability of DOSPERT varied significantly across the domain scales and was low for the ethical, health and social domains. There are several factors that may contribute to the low reliability of these DOSPERT scales.…”
Section: Domain-specific Risk Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its popularity, several measurement issues regarding the internal structural validity of the DOSPERT have been found. The meta-analysis by Shou and Olney (2020a) found that the reliability of DOSPERT varied significantly across the domain scales and was low for the ethical, health and social domains. There are several factors that may contribute to the low reliability of these DOSPERT scales.…”
Section: Domain-specific Risk Attitudesmentioning
confidence: 99%
“…Some authors, although defining risk in terms of outcome variability, develop scales in which many of the items focus on potential danger or loss (e.g., General Risk Propensity Scale: Zhang, Highhouse & Nye, 2018; Passive Risk Taking Scale: Keinan & Bereby-Meyer, 2012). Thus, researchers that are interested in measuring risk attitudes create items that focus either on attitudes toward situations that entail uncertainty (chance-based outcomes) or loss outcomes (Shou & Olney, 2020a). In the present article, we define risk as the possibility of having "negative consequences", experienced as a loss, to more closely align with the conceptualization prevalent in the health and clinical psychology literatures, which include many of the popular self-report measures of risk attitudes in the literature.…”
mentioning
confidence: 99%
“…Given that just over half of the participants completed the modified risk propensity scale, we were unable to examine sex differences and association with HG, however there was no correlation between frequency of head/neck or body contacts and risk propensity for the overall sample. Other more comprehensive risk taking scales [e.g., the Domain-Specific Risk Taking Measure; 48 ] may have enabled a more in-depth analysis of this concept, however such scales are not designed for use with paediatric cohorts. Certainly sex differences in safety behavior and risk taking in contact sports such as Australian football requires greater investigation given the recent proliferation in female participation [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the quantitative nature of these decisions, as well as their ability to be adapted to a laboratory task and setting. But evidence from the domain-specific risk-taking scale (DOSPERT) suggests that risk perception and risk-taking behavior depends on the type of decision an individual is making (Blais & Weber, 2006;Shou & Olney, 2020). This may be especially relevant for uncertainty, which may arise from different sources depending on the domain.…”
Section: Domain-specificitymentioning
confidence: 99%